PENGARUH MEDIA FILM TERHADAP HASIL BELAJAR PESERTA DIDIK - Afdol, Abdul; Mahruddin, Amir (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2015)
The problem identified in this study is the difference that caused student learning outcomes vary greatly, formative test results are very low, the lack of using media in learning, and learning more using the lecture method. The limitation of this study is a problem in the Media Film effect toward studentsâ outcomes on learning Islamic Education in Fourth Grade of Elementary School at District Cilangkap 5, Depok. Thus, in relation to the restriction of the above problems, the formulation of the problem is "How is the influence of Media Film to Improve Studentsâ Learning Outcomes in Learning Islamic Education of Fourth Grade of Elementary School at District Cilangkap 5, Depok? In the study researcher used random sampling technique which is a technique for taking individual samples of the population by means of random or indiscriminate. So, in this technique all individuals in the population either individually or jointly given the same opportunity to become members of the sample assigned. Before further analyzing on the raw data, researchers perform firstly instrument tests through validity and reliability test, as well as through the analysis prerequisite tests, which are normality, homogeneity and linearity tests, and for the last researchers used data analysis techniques using linear regression formula and analysis variants (ANOVA). Finally, this research can be concluded that there is positive and significant relationship between the use of media film (variable X) with studentsâ learning outcomes on the subject of Islamic Education (variable Y) in the fourth grade student in Elementary School of Dictrict Cilangkap 5, Depok. With levels of correlation indicated by the correlation coefficient r xy of 0448. RÂ²xy amounted to 0,201, which means that the effect of the use of the media film in learning a contribution of 20% of the learning outcomes of Islamic Education subject. Then obtained Freg price of 9.523 when compared with Ftable with db=1 versus 38 where Ft (0,05) = 4.10, and the price of Ft (0,01) = 7.35, the price Freg> Ft (0.05) and Freg> Ft (0.01), so it is declared significant, so the influence of the film media on learning on learning outcomes of Islamic religious education learners Elementary School fourth grade Cilangkap 5 Depok recognized by 20% or hypothesis are approved.